First occurrence of Beroe forskalii (Ctenophora) in South American Atlantic coastal waters, with notes on the use of macrociliary patterns for beroid identification - Oliveira, Otto M.p.; Migotto, Alvaro E. (Zootaxa, 2014)
Beroe forskalii Milne Edwards, 1841 is an oceanic ctenophore with a global distribution. The present study provides the first record of Beroe forskalii for the South American Atlantic coast, including a redescription of the species and a discussion on the utility of macrociliary patterns for the correct identification of at least some beroid species, exemplified by a comparison of the macrociliary patterns of Beroe forskalii and Beroe ovata (Chamisso & Eysenhardt, 1821).